Stress Analysis of Fiber-reinforced Composite Built-up Beam Using the Unit Cell Method - Hussain, Haydar A.; Hussain, Ala a M.; Ali, Luay M. (Nahrain University College of Engineering Journal, 2008)
Macro- and microscopic levels of analyses are used to capture the behavior of a built-in beam made of a unidirectional fiberreinforced polymeric material. Finite element formulation basing on the displacement approach and minimum potential energy principle is carried out in the longitudinal direction of the beam to determine thevertical displacements (deflections) at various sections, stresses and strains. A unit cell method in micromechanical analysis based on the finite element method is used to define the state and distribution of the stresses induced in transverse sections. Hexagonal fiber-matrix packing system is idealized for the problem. The package of ANSYS 5.4 and a Matlab program are usedto solve for the macro- and micromechanical analyses. To examine the validity of the presented method, it is applied to analyze a beam made of matrix and fibers with the same elastic properties the results are then compared with those obtained by using a method used for isotropic materials given that properties , the convergence noticed is verifying the validity of the analysis method adopted by the current work